2014
DOI: 10.3390/molecules190811333
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Novel Triazole Compounds Containing Piperazine Moiety

Abstract: Design and synthesis of triazole library antifungal agents having piperazine side chains, analogues to fluconazole were documented. The synthesis highlighted utilization of the click chemistry on the basis of the active site of the cytochrome P450 14α-demethylase (CYP51). Their structures were characterized by 1 H-NMR, 13 C-NMR, MS and IR. The influences of piperazine moiety on in vitro antifungal activities of all the target compounds were evaluated against eight human pathogenic fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…8,9) Moreover, CYP51 has been regarded by many researchers as a target for molecular docking and widely applied in the rational design of antifungal compounds. [10][11][12][13][14][15] Studies showed that 16) the antifungal triazoles featured a core structure composed of a triazole, a halophenyl ring, while differing in the side chains. The development of triazole drugs is primarily driven through structure optimization especially of the side chains as well as structure-activity relationship (SAR) study.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Moreover, CYP51 has been regarded by many researchers as a target for molecular docking and widely applied in the rational design of antifungal compounds. [10][11][12][13][14][15] Studies showed that 16) the antifungal triazoles featured a core structure composed of a triazole, a halophenyl ring, while differing in the side chains. The development of triazole drugs is primarily driven through structure optimization especially of the side chains as well as structure-activity relationship (SAR) study.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, azole system is a structural element of many drugs that have antifungal activity such as fluconazole 6, itraconazole, voriconazole and posaconazole are widely used for treatment of invasive fungal infections (IFIs) [22]. They exerted their antifungal activity by inhibition of ergosterol synthesis, a major component of fungal membrane, through blocking the P450dependent enzyme, lanosterol 14-α-demethylase (CYP 51) [22], where the azole ring bonded to the heme iron of CYP 51. Lack of ergosterol and accumulation of 14-α-demethylase lead to loss of the function of several enzymes located in membrane that result in inhibition of fungal growth and DNA replication [23].…”
Section: Introductionmentioning
confidence: 99%
“…SAR study of the different antifungal agents indicates that the triazole ring, the difluorophenyl group, and the hydroxyl group are the important pharmacophores for the antifungal activity. Development in biological and pharmacological activities against resistant fungal strains can be obtained by modification of substituents on their side chain [22]. Similarly, 1,3,4oxadiazole as a bioisoster of 1,2,4 triazole represents an important motif in medicinal chemistry, some 1,3,4-oxadiazole derivatives experienced good antifungal activity when bonded to fluoroquinolones [36 , 37].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin derivatives incorporating the 1,2,3-triazole moiety showed antifungal activity [32]. Hybrids of fluconazole with 1,2,3-triazole were proved to possess satisfactory activity [33].…”
Section: Introductionmentioning
confidence: 99%